Editorial: New approaches to pest control - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
Insect pests reduce global food output by 25% to 35%, in spite of pesticide applications costing some US$ 32 billion annually.